Citizenship in the Arab World Kin, Religion and Nation-State - Parolin, Gianluca P. (Amsterdam University Press, 2009)
The book is the fruit of five years of on-site research on citizenship in the Arab world. It takes a broader legal perspective to the multifaceted reality of nationality and citizenship. The methodology employed builds on the interdisciplinary approach of comparative legal studies, and brings in theories, concepts and insights from anthropology, political science, Arab and Islamic studies, linguistics and sociology. The work relies on a broad range of Western and Arab references, and all sources and documents were directly accessed in their original languages; this is particularly relevant for Arab legislation (all in-text reference has been translated by the author, and the original has been inserted using scientific transliteration).